2020
DOI: 10.3897/neobiota.54.38584
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and management of Solenopsis invicta in China

Abstract: Red imported fire ant, Solenopsis invicta, was first found in Taiwan province of China in 2003. To prevent transboundary expansion, the Chinese government has formulated various control strategies in the last 15 years to slow down the spread of S. invicta. Despite all efforts, S. invicta invasion has reached more than 390 counties of 13 provinces and two special administrative regions in China; at present, S. invicta remains at the stage of rapid expansion. The transnational entry of S. invicta is linked to im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 86 publications
1
37
0
2
Order By: Relevance
“…The red imported fire ant, Solenopsis invicta Buren, is native to inner South America and has been introduced to the United States, Australia, China, Japan, and many other regions in the world. [1][2][3][4] Solenopsis invicta stings cause serious medical problems, such as severe infections, fever, generalized urticaria, anaphylactic shock, and even death. 5,6 People with limited mobility are under high risk of indoor S. invicta attack (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The red imported fire ant, Solenopsis invicta Buren, is native to inner South America and has been introduced to the United States, Australia, China, Japan, and many other regions in the world. [1][2][3][4] Solenopsis invicta stings cause serious medical problems, such as severe infections, fever, generalized urticaria, anaphylactic shock, and even death. 5,6 People with limited mobility are under high risk of indoor S. invicta attack (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…RIFA is a major aggressive invasive ant species worldwide and has been categorized as a “super pest” owing to its expansion rate and severe effects on the nation’s economy, health, ecology, and lifestyle [ 39 , 40 , 41 ]. Despite great efforts, the United States has failed to eliminate RIFA, in part due to the lack of experience and absence of effective natural enemies [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, RIFA was thought to have arrived in 1933 in the United States but was not discovered until 1942 [ 42 ]. The cases in Taiwan, China, and Australia were similarly discovered late [ 41 ]. RIFA was likely present in Taiwan for more than five years before it was discovered in 2003 [ 3 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twelve colony groups of S. invicta were collected between 25 May and 11 June 2018. Previous studies have shown that the polygyne type is the dominant social form of S. invicta in mainland China (Wang et al ., 2020). In this study, all S. invicta colonies were considered polygyne because of the relatively high density of mounds observed at the collection site.…”
Section: Methodsmentioning
confidence: 99%